Anti-tumor activity of a novel compound-CDF is mediated by regulating miR-21, miR-200, and PTEN in pancreatic cancer. - Bin Bao; Shadan Ali; Dejuan Kong; Sanila H Sarkar; Zhiwei Wang; Sanjeev Banerjee; Amro Aboukameel; Subhash Padhye; Philip A Philip; Fazlul H Sarkar (PLoS ONE)
Background The existence of cancer stem cells (CSCs) or cancer stem-like cells in a tumor mass is believed to be responsible for tumor recurrence because of their intrinsic and extrinsic drug-resistance characteristics. Therefore, targeted killing of CSCs would be a newer strategy for the prevention of tumor recurrence and/or treatment by overcoming drug-resistance. We have developed a novel synthetic compound-CDF, which showed greater bioavailability in animal tissues such as pancreas, and also induced cell growth inhibition and apoptosis, which was mediated by inactivation of NF-κB, COX-2, and VEGF in pancreatic cancer (PC) cells. Methodology/principal findings In the current study we showed, for the first time, that CDF could significantly inhibit the sphere-forming ability (pancreatospheres) of PC cells consistent with increased disintegration of pancreatospheres, which was associated with attenuation of CSC markers (CD44 and EpCAM), especially in gemcitabine-resistant (MIAPaCa-2) PC cells containing high proportion of CSCs consistent with increased miR-21 and decreased miR-200. In a xenograft mouse model of human PC, CDF treatment significantly inhibited tumor growth, which was associated with decreased NF-κB DNA binding activity, COX-2, and miR-21 expression, and increased PTEN and miR-200 expression in tumor remnants. Conclusions/significance These results strongly suggest that the anti-tumor activity of CDF is associated with inhibition of CSC function via down-regulation of CSC-associated signaling pathways. Therefore, CDF could be useful for the prevention of tumor recurrence and/or treatment of PC with better treatment outcome in the future.